When Sustainability Becomes Instagrammable: Extending the Source Credibility Model to Green Influencer Marketing in New Media - Harikumar, Attchaya; Swaminathan, Usha (International Review of Management and Marketing, 2026)
Employing the heuristic-systematic information processing model (HSM), this study aims to add engagement as a new dimension in Ohanian’s classic Source Credibility Model (SCM). It further demonstrates its relevance through a mediation framework where content-focused messaging mediates greenfluencers’ (sources) attributes and credibility in greenfluencer advertisements (CGA), i.e., sponsored green posts published through their profiles. Indian social media users who are also the followers of greenfluencers on Instagram are the target population. A cross-sectional mixed-methods approach is employed to confirm the scale items, and PLS-SEM was used to test the hypotheses. Results show that the classic attributes such as “attractiveness, trustworthiness, and expertise” are still significant for endorsers in new media. Additionally, the dimension of engagement enhances the model for new media applications, where it has emerged as a crucial source cue. It further shows that CGA is not merely a direct effect of source cues. But rather, it is mediated through content-focused messaging where source cues gain persuasive power only when embedded with message content. The study sheds light on Indian consumers’ perceptions of CGA in new media. There are significant theoretical contributions by acknowledging the instant interaction affordance of new media to the literature on source credibility, persuasion in new media, and digital consumer behavior.